2016
DOI: 10.1007/s00421-016-3397-8
|View full text |Cite
|
Sign up to set email alerts
|

Implementing intelligent physical exercise training at the workplace: health effects among office workers—a randomized controlled trial

Abstract: High intensity IPET combined with the recommendations of moderate intensity physical activity demonstrated significant clinical relevant improvements in CRF and systolic blood pressure. This underlines the effectiveness of health promotion by implementing physical exercise training at the workplace.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
53
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(58 citation statements)
references
References 39 publications
2
53
0
Order By: Relevance
“…Weight loss and weight gain have been reported, but other health outcomes are often also positively influenced . Five studies included in the present review were designed to examine the effects of combined or concurrent aerobic and resistance exercise protocols . Clinically relevant individual response variability was present in just one trial of an intervention involving 12 months of 1 h per week combined aerobic and circuit‐style training ( n = 193), alongside recommendations to undertake 30 min of exercise, 6 d per week, compared with a non‐exercise control group ( n = 194) .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Weight loss and weight gain have been reported, but other health outcomes are often also positively influenced . Five studies included in the present review were designed to examine the effects of combined or concurrent aerobic and resistance exercise protocols . Clinically relevant individual response variability was present in just one trial of an intervention involving 12 months of 1 h per week combined aerobic and circuit‐style training ( n = 193), alongside recommendations to undertake 30 min of exercise, 6 d per week, compared with a non‐exercise control group ( n = 194) .…”
Section: Discussionmentioning
confidence: 99%
“…Five studies included in the present review were designed to examine the effects of combined or concurrent aerobic and resistance exercise protocols . Clinically relevant individual response variability was present in just one trial of an intervention involving 12 months of 1 h per week combined aerobic and circuit‐style training ( n = 193), alongside recommendations to undertake 30 min of exercise, 6 d per week, compared with a non‐exercise control group ( n = 194) . Mean weight change was −0.49 kg in the intervention group versus 0.08 kg in control, with SD of the changes of 3.32 and 2.97 kg, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since, one of the main pillars of CR is exercise training, mainly dynamic and aerobic exercise have been related with increased of cardiorespiratory fitness. 10,11 Bauer et al 12 have demonstrated exercise training improves glucose metabolism, insulin signalling, lipid profile, endothelial function, and blood pressure as well as exercise tolerance, in both diabetic and non-diabetic patients. However, in diabetic patients these parameters were remarkably improved.…”
Section: Discussionmentioning
confidence: 99%